2022
DOI: 10.1002/hep.32453
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent large spontaneous portosystemic shunt embolization for the prevention of overt hepatic encephalopathy after TIPS: A randomized controlled trial

Abstract: Background and Aims Large spontaneous portosystemic shunt (SPSS) is associated with increased risk of HE in patients undergoing transjugular intrahepatic portosystemic shunt (TIPS). This study aimed to evaluate whether prophylactic embolization of large SPSS at the time of TIPS creation could reduce the incidence of post‐TIPS HE in patients with cirrhosis and variceal bleeding. Approach and Results From June 2014 to August 2017, 56 patients with cirrhosis and large SPSS planning to undergo TIPS for the prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
1
41
1
Order By: Relevance
“…with particular reference to overt HE history 192 ; liver and kidney function, focusing on bilirubin levels, international normalised ratio and urea levels 193 ; a neurological and neuropsychological examination to detect HE, to rule out and manage large spontaneous porto-systemic shunts 194 ; and, finally, microbiome analysis could also help with decision-making in patients with TIPS at risk of overt HE. 195 In summary, new bouts of post-TIPS HE could be modulated by using covered stents 196 and promoting early placement of TIPS.…”
Section: Recommendationmentioning
confidence: 99%
“…with particular reference to overt HE history 192 ; liver and kidney function, focusing on bilirubin levels, international normalised ratio and urea levels 193 ; a neurological and neuropsychological examination to detect HE, to rule out and manage large spontaneous porto-systemic shunts 194 ; and, finally, microbiome analysis could also help with decision-making in patients with TIPS at risk of overt HE. 195 In summary, new bouts of post-TIPS HE could be modulated by using covered stents 196 and promoting early placement of TIPS.…”
Section: Recommendationmentioning
confidence: 99%
“…On the other hand, the presence of large SPSS increases the risk of post-TIPS overt hepatic encephalopathy [ 21 ]. Recently, a randomized controlled trial demonstrates that prophylactic embolization of large SPSS during TIPS procedures can reduce the risk of overt hepatic encephalopathy without any increased risk of other liver-related complications [ 31 , 32 ]. These findings supported embolization of varices and SPSS during TIPS procedures.…”
Section: Therapeutical Implicationsmentioning
confidence: 99%
“…42 The existence and diameter of the portosystemic shunt (SPSS) is an independent predictor of post-TIPSS hepatic encephalopathy. 43 A recent randomized trial by Lv et al 44 reported a lower risk of HE following TIPSS with concurrent embolization of a large spontaneous portosystemic shunt in patients undergoing TIPSS. Following embolization of large collaterals, the amount of blood shunting through TIPSS was reduced, as it was limited by the diameter of the TIPSS, which is often smaller than the co-existing large SPSS.…”
Section: Pre-emptive Tipss: the Way Forwardmentioning
confidence: 99%